PERANCANGAN DATA WAREHOUSE dan DASHBOARD PT XYZ - I Dewa Bagus Gde Khrisna Jayanta Nugraha; Agus Susanto; Abba Suganda Girsang (ITP Press, 2022)
A contractor is a company that contracts with another person or government or company to supply goods or complete certain services. PT. XYZ has a lot of project contract data and it has not yet been processed into information. To facilitate the employees of PT. XYZ in analyzing and evaluating past or future projects requires a Data Warehouse. The purpose of this research is to design and analyze the data warehouse needed to provide information regarding project contract data at PT. XYZ. The data warehouse design method uses 4 stages (Four-Step Methodology) proposed by Ralph Kimball in designing a data warehouse system. The final result to be achieved is the design of a data warehouse and dashboard is a visualization that will provide significant information about the project contract data at PT. XYZ which can be seen from different perspectives and facilitates related parties in making decisions.